Preparation and Characterization of Silver Nanoparticles and its Medical Application against Pathogenic Bacteria - Azhin Zainel Abbas; Rosure Borhanalden Abdulrahman; Thikra A. Mustafa (مجلة بغداد للعلوم)
The fabrication of Solid and Hollow silver nanoparticles (Ag NPs) has been achieved and their characterization was performed using transmission electron microscopy (TEM), zeta potential, UV–VIS spectroscopy, and X-ray diffraction (XRD). A TEM image revealed a quasispherical form for both Solid and Hollow Ag NPs. The measurement of surface charge revealed that although Hollow Ag NPs have a zeta potential of -43 mV, Solid Ag NPs have a zeta potential of -33 mV. According to UV-VIS spectroscopy measurement Solid and Hollow Ag NPs both showed absorption peaks at wavelengths of 436 nm and 412 nm, respectively. XRD pattern demonstrates that the samples' crystal structure is cubic, similar to that of the bulk materials, with average particle sizes of 28 nm and 27 nm for Solid and Hollow Ag NPs, respectively. The antimicrobial activity of synthesized Ag NPs was tested on some pathogenic bacterial strains which were isolated from urinary tract infection (UTI) and burn infection. The experiment results showed positive bactericidal activity against isolated bacteria with Solid Ag NPs which were most effective against both G-ve and G+ve bacteria. In addition, solid nanoparticles showed time and concentration dependent antibacterial activity.